Channel Characterization for 700 MHz DSRC Vehicular Communication - Raffi Sevlian; Carl Chun; Ian Tan; Ahmad Bahai; Ken Laberteaux (Journal of Electrical and Computer Engineering)
Adapting OFDM for vehicular communication requires extensive knowledge of anticipated multipath and Doppler environments. We present a GPS-enabled channel sounding system built and used to conduct a channel measurement campaign. Tests conducted at the 700 MHz band in and around downtown Ann Arbor, Michigan, explored various vehicle-to-vehicle and vehicle-to-roadside channel scenarios. The measured channel metrics are used to quantify the effects on guard interval, packet duration, and subcarrier spacing for a functional OFDM system at 700 MHz. This paper is one of the first to present vehicular-based channel-modeling results from measured data in the 700 MHz band.